HIV, livelihoods, food and nutrition security - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
A combination of new and ongoing forces is driving global food prices. Rising energy prices and subsidized biofuel production, income and population growth, globalization, and urbanization are among the major forces contributing to surging demand—while on the supply side, land and water constraints, underinvestment in rural infrastructure and agricultural innovation, lack of access to inputs, and weather disruptions are impairing productivity growth and the needed production response. According to IMF data, rice and wheat prices soared in late 2007 and early 2008—up 60% and 89% respectively over 2007 levels.